Age-Related Viability of Patients with Ophthalmopathology Depending on Age Dissociation - O. L. Fabrikantov; A. E. Kopylov; N. M. Agarkov; N. V. Popova; D. R. Shmarova (Oftalʹmologiâ, 2024)
Diabetic retinopathy and senile cataracts cause not only a significant impairment of visual functions, but also can affect the psychological and emotional status of patients and their age-related viability, which has not been practically studied in patients with the abovementioned ophthalmological diseases.The purpose: to study age–related viability in patients with ophthalmopathology depending on age dissociation. Age viability was studied among 135 patients aged 60–74 years with diabetic retinopathy and cataract with coincidence of calendar and biological age and 142 patients aged 60–74 years with diabetic retinopathy and cataract with accelerated biological age. It was found that diabetic retinopathy and cataract cause a more significant decrease in age viability in patients with an excess of the biological age of the chronological age to 60,1 ± 1,7 points versus 76,4 ± 1,5 points (p < 0,001) in diabetic retinopathy and cataract with the coincidence of biological and calendar age. A similar effect was found for the somatic component of age-related viability, which in patients with diabetic retinopathy and cataract with an excess of the biological age of the chronological value was 4,2 ± 0,5 points relative to 2,2 ± 0,4 points (p < 0,01) in patients with diabetic retinopathy and cataract, who had a coincidence of biological and calendar age. Diabetic retinopathy and cataracts are most affected when the biological age of the calendar value is exceeded among the subdomains of age viability, such as relationship security and positivity of accepted changes, resistance to adverse influences and trust in personal instincts with a significant difference between groups. Diabetic retinopathy and cataracts in patients with exceeding the biological age of the calendar significantly reduce age viability.